(untitled) - Copeland, Lori; Smith, Virginia; 1960- (Harvest House Publishers, 2012)
Young Amish woman Rachel Switzer comes to 1880s Lawrence, Kansas in pursuit of cowboy Jesse Montgomery, only to be caught in the middle of a temperance riot and mistakenly arrested by sheriff Colin Maddox.
Keywords: Amish; Kansas; Fiction; Sheriffs; Fiction; Young women; Fiction; Western stories; Love stories; Christian fiction